2020
DOI: 10.1007/s10479-020-03666-w
|View full text |Cite
|
Sign up to set email alerts
|

A data-driven forecasting approach for newly launched seasonal products by leveraging machine-learning approaches

Abstract: Companies in the fashion industry are struggling with forecasting demand due to the short-selling season, long lead times between the operations, huge product variety and ambiguity of demand information. The forecasting process is becoming more complicated by virtue of evolving retail technology trends. Demand volatility and speed are highly affected by e-commerce strategies as well as social media usage regards to varying customer preferences, short product lifecycles, obsolescence of the retail calendar, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Traditional demand forecasting methods predict future values based on time series that analyze limited historical demand data. Some of them include Delphi method, grass roots forecasting, trend analysis, multi-regression model, moving averages, Croston's method, time series model, exponential correction and ARIMA (Alon et al, 2001;Bollapragada et al, 2008;Chen et al, 2000;Kharfan et al, 2020). These methods have been found to be effective only when factors such as nature trends and seasonal factors are not considered.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional demand forecasting methods predict future values based on time series that analyze limited historical demand data. Some of them include Delphi method, grass roots forecasting, trend analysis, multi-regression model, moving averages, Croston's method, time series model, exponential correction and ARIMA (Alon et al, 2001;Bollapragada et al, 2008;Chen et al, 2000;Kharfan et al, 2020). These methods have been found to be effective only when factors such as nature trends and seasonal factors are not considered.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given the predictive ability of ML, one of the most prominent problems of marketing is to improve demand forecasting as this is vital for customer satisfaction, product planning and supply chain management (Boone et al, 2019;Carbonneau et al, 2008;Kharfan et al, 2020;Zhu et al, 2021) and predict the stock market movement (Eachempati et al, 2021). ML uses several forecasting methods such as Neural Network, Fuzzy Neural Network, Artificial Neural Network, Recurrent Neural Networks, Genetic Algorithm, Support Vector Regression, Random Forest Regressor, Decision Tree Regressor etc.…”
mentioning
confidence: 99%
“…For example, Huber and Stuckenschmidt (2020) provided evidence that global ML models (feed-forward and recurrent neural networks, gradient boosted regression trees) could achieve a higher forecast accuracy compared to time series models with adjustments or a regularised linear regression model, and the ranking of the evaluated methods remained constant over different horizons. Kharfan, Chan, and Efendigil (2020) applied an ML pipeline comprising clustering, classification and prediction to forecast newly launched fashion products. Punia, Singh, and Madaan (2020) calculated coherent hierarchical forecasts in a multidimensional hierarchy comprising location, product and online vs. offline channels, again using an LSTM.…”
Section: Methodological Developmentsmentioning
confidence: 99%
“…The qualitative approach involves individual perception to figure out the unusual data points and adjust them before the data were processed quantitatively (Pradita et al, 2020). Kharfan, Chan, and Efendigil (2021) studied a data-driven methodology to improve the demand forecasting procedure for fashion retailers for recently launched products without historical data in a vigorous market situation. The results showed that the three-step model delivers visibility of core factors that influence demand through clustering and classification.…”
Section: (Neisyafitri and Ongkunaruk)mentioning
confidence: 99%